A just transition towards sustainable development: A legal analysis of the transition to a low-carbon economy in the South African mining industry in the context of sustainable development. - Zondo, Nondumiso (Department of Private Law, 2025)
Section 100 of the Mineral and Petroleum Resources Development Act 28 of 2002 (MPRDA) mandates the Broad-Based Socio-economic Empowerment Charter for the Mining and Minerals Industry (the Mining Charter) to outline how the MPRDA's objectives of redressing historical social and economic inequities can be met. However, the MPRDA does not require that environmental protection be included as one of the fundamental concerns to be addressed by the Mining Charter. Thus, the resulting Mining Charter does not establish a framework for achieving environmental objectives. Environmental justice redresses the injustices of the past that are associated with the inequality that resulted from economic growth which caused environmental degradation and pollution, as well as the distorted access to and benefits from the extraction and use of natural resources. This leads us to the central question of this study: Can the Mining Charter do more to promote sustainable development in the mining industry in the context of an energy transition? Section 24 of the Constitution of the Republic of South Africa of 1996 declares environmental justice as a national priority, encouraging the mainstreaming of environmental protection measures into legislation to promote sustainable development and use of natural resources while promoting socioeconomic development. This research argues that the lack of environmental mandate in the Mining Charter is a point of concern for its effectiveness in addressing 'historical social and economic inequalities'. This research offers insight into the challenges presented by not incorporating climate change and environmental justice into regulations, which ignores a host of social, economic, and environmental vulnerabilities that will be brought about by climate change, especially on the historically disadvantaged whom it claims it aims to redress. This research is premised on the conviction that social and economic justice cannot be achieved without environmental and climate justice